2017
DOI: 10.1097/md.0000000000008283
|View full text |Cite
|
Sign up to set email alerts
|

The association of genetic variants in chemokine genes with the risk of psoriasis vulgaris in Chinese population

Abstract: This study aimed to investigate the influence of polymorphisms in chemokine genes, including MCP1, CCR2, and CCR5 with psoriasis vulgaris (PV) risk in a Chinese population.The genotyping of studied polymorphisms through polymerase chain reaction (PCR) and sequencing was conducted in 142 PV patients and 147 healthy controls. The genotype distribution of the polymorphisms in the control group was checked to determine whether it conformed to Hardy–Weinberg equilibrium (HWE). The genotype and allele frequencies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The CCL2 rs1024611 polymorphic site is located in the promoter region of the CCL2 gene, where an A>G substitution can lead to the upregulation of its expression in vivo (20). This polymorphism has been reported to participate in various diseases, such as breast cancer ( 7), IgA nephropathy (8) and psoriasis vulgaris (21). The association between the CCL2 rs1024611 polymorphism and prostate cancer risk has been examined in several studies, but none have been able to demonstrate a significant link (11,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCL2 rs1024611 polymorphic site is located in the promoter region of the CCL2 gene, where an A>G substitution can lead to the upregulation of its expression in vivo (20). This polymorphism has been reported to participate in various diseases, such as breast cancer ( 7), IgA nephropathy (8) and psoriasis vulgaris (21). The association between the CCL2 rs1024611 polymorphism and prostate cancer risk has been examined in several studies, but none have been able to demonstrate a significant link (11,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The CCR2 rs1799864 polymorphism is a non-synonymous mutation in exon 2, resulting in substitution of the amino acid valine with isoleucine at position 64 (22). Previous studies have reported that this genetic variation is a risk factor for psoriasis vulgaris (21), ischemic stroke (23) and carotid atherosclerosis (24). However, in the present analysis, the polymorphism rs1799864 in CCR2 was not associated with BPH susceptibility in either the genotype or the allelic form, in agreement with the study by Singh et al (25).…”
Section: Discussionmentioning
confidence: 99%
“…Pruritus is an unpleasant sensation with a desire to scratch and is one of the common symptoms of many primary and systemic skin diseases, with an incidence of 62% to 97% in patients with psoriasis. [ 15 , 16 ] Patients with psoriasis have a high frequency and pronounced rash with a long duration, which is not life-threatening but affects aesthetics and skin function and can even lead to anxiety and depression. [ 17 ] The clinical treatment of psoriasis is aimed at controlling and stabilizing the disease, reducing adverse effects and improving quality of life.…”
Section: Discussionmentioning
confidence: 99%